Electrochemical preparation method of carbon-supported nickel-iron double metal hydroxide catalyst for electro-reduction of nitrate to synthesize ammonia
By depositing carbon-supported nickel-iron bimetallic hydroxide catalysts on the surface of carbon paper, the selectivity and stability of existing electrocatalytic nitrate synthesis ammonia catalysts are solved, and efficient ammonia synthesis and long-term cycle stability are achieved, which improves the stability of Properties of nitrate synthesis of ammonia.
Patent Information
- Application Number
- CN202211658014.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The existing catalysts for electrocatalyzing nitrate synthesis of ammonia have problems such as low reaction selectivity, poor corrosion resistance and poor cycle stability, which leads to low Faraday efficiency and poor stability, which hinders the further development of ammonia synthesis of nitrate.
Using carbon-supported nickel-iron bimetal hydroxide catalyst, nickel-iron bimetal hydroxide is deposited on the surface of carbon paper by electrochemical preparation, and using oxygen vacancy and defect positions of carbon paper and surface modification of additives to form a sheet-like shape The coronal structure inhibits hydrogen evolution side reactions and improves the selectivity and circulation stability of NO3RR.
It significantly improves the Faraday efficiency and yield of ammonia, extends the cycle stability of the catalyst, is suitable for long-term NO3RR processes, avoids interference from side reactions, and improves the selectivity of nitrate synthesis of ammonia.
Smart Images

Figure CN115786959B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrochemical preparation method of a carbon-supported nickel-iron double metal hydroxide catalyst for electro-reduction of nitrate to synthesize ammonia, and belongs to the fields of chemical industry and electrocatalysis. Background Art
[0002] As an important chemical raw material, ammonia has important applications in fertilizers, hydrogen storage, coatings and other fields. At present, the main method for synthesizing ammonia in industry is the Haber-Bosch method, which reacts under high temperature and high pressure (400-600℃, 150-300atm), consumes a large amount of fossil energy (about 2% of global energy consumption each year), and the combustion of fossil energy causes the reaction to emit a large amount of greenhouse gases, causing negative effects such as global warming. In recent years, the artificial synthesis of NH3 by electrochemical methods has become a hot frontier research field. The electrochemical synthesis of ammonia technology uses wind power and photovoltaic power supply, uses water as a hydrogen source, significantly reduces carbon dioxide emissions, reacts at room temperature and pressure, and has no difficult-to-handle by-products. However, when nitrogen is used as the nitrogen source, the solubility of N2 in water is poor, the N≡N bond energy is strong and difficult to activate, and the limitation of the competitive hydrogen evolution reaction (HER) makes the NH3 yield extremely low (about 0.1-100μg h -1 mg cat -1 ), so this new technology still cannot be used for large-scale production of NH3. Although researchers have proposed a variety of methods such as surface vacancy engineering, surface molecular grafting, internal electric field regulation, and new three-phase system to improve the efficiency of the entire system in synthesizing ammonia, there is still a long way to go before it can be applied on a large scale.
[0003] As mentioned above, the nitrogen-nitrogen triple bond (942 kJ / mol) in nitrogen has strong bond energy, stable binding, and is difficult to activate. If abundant nitrates and nitrites are used as nitrogen sources, from a thermodynamic point of view, the nitrogen-oxygen double bond (607 kJ / mol) has lower bond energy and is easier to activate and dissociate, so the reaction activation energy is lower. From a kinetic point of view, nitrates and nitrites have higher solubility and faster mass transfer rate, so they can significantly improve the efficiency of ammonia production. In addition, nitrates and nitrites are widely present in polluted water systems. If they are reduced by electrochemical methods, pollutants can be removed and high value-added product ammonia can be obtained. At present, most catalyst research on the electroreduction of nitrates to synthesize ammonia (NO3RR) system focuses on metal-based catalysts (precious metals, alloys, metal oxides, etc.). For this type of catalyst, there are two problems that seriously affect the reaction efficiency: first, various metals are more easily corroded, especially in acidic or alkaline electrolysis systems, and their stability is poor, which hinders their large-scale application; second, during the reaction of such metal-based catalysts, the two-electron transfer hydrogen evolution reaction (HER, 2H + +2e -→H2) is the NO3RR reaction with 8 electron transfer (NO3RR, NO3 - +9H + +8e - →NH3+3H2O), the competitive reaction of NO3RR with nitrate synthesis was hindered by the faster kinetic reaction rate of hydrogen evolution reaction, which resulted in low Faradaic efficiency and poor stability of NO3RR.
[0004] In summary, the catalysts used in electrocatalytic nitrate synthesis of ammonia are mostly metal catalysts, which have low reaction selectivity, poor corrosion resistance, poor cycle stability, etc., which ultimately lead to poor selectivity and stability of NO3RR, hindering the further development of NO3RR process. In order to overcome the shortcomings of the prior art, this application proposes to use carbon paper as a conductive substrate, and use highly selective nickel-iron bimetallic hydroxide loaded on the surface of carbon paper as a monolithic catalyst to drive NO3RR synthesis of ammonia; provide an electrochemical preparation method of carbon-loaded nickel-iron bimetallic hydroxide catalyst for electrocatalytic nitrate synthesis of ammonia, avoid the strong competition of side reactions HER and other problems, and improve NO3RR selectivity. Summary of the invention
[0005] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an electrochemical preparation method of a carbon-supported nickel-iron double metal hydroxide catalyst for electrocatalytic nitrate reduction to synthesize ammonia, so as to alleviate the competitive interference of the side reaction HER in the NO3RR process and ultimately improve the NO3RR selectivity.
[0006] In order to achieve the above-mentioned invention object and solve the problems existing in the prior art, the technical solution adopted by the present invention is:
[0007] An electrochemical preparation method of a carbon-supported nickel-iron double hydroxide catalyst for electrocatalytic nitrate reduction to synthesize ammonia, comprising the following steps:
[0008] Step 1, dissolve nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride (ammonium bifluoride), and urea (sodium hydroxide) in deionized water, and use a magnetic stirrer to quickly stir and uniformly obtain a mixed solution, wherein the concentrations of nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride, and urea in the solution are 0.4-0.8mM, 0.2-0.8mM, 1.0-2.0mM, and 4mM, respectively. Wherein, the nickel nitrate hexahydrate can be replaced by nickel sulfate or nickel acetate; the ferric nitrate nonahydrate can be replaced by ferric sulfate, ferric acetate, or ferric chloride; the ammonium fluoride can be replaced by ammonium bifluoride, ammonium chloride, sodium fluoride, or sodium chloride; and the urea can be replaced by sodium hydroxide.
[0009] Step 2: Assemble an electrode with 2cm×3cm hydrophilic carbon paper as cathode plate, 2cm×2cm commercial platinum sheet electrode as anode plate, Ag / AgCl as reference electrode (filling liquid is saturated KCl solution) and electrochemical workstation (CHI660E) into an electrodeposition cell. The hydrophilic carbon paper includes carbon cloth and carbon fiber.
[0010] Step 3, adding the mixed solution to a pre-assembled electrodeposition cell, setting the voltage to -1V to -2V, the temperature to 25°C, and carrying out the electrodeposition reaction in a constant voltage manner for a deposition time of 5-60min. After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, placed in a 60° oven and dried for 6h, then taken out and weighed, and the deposition load is calculated to obtain the carbon-supported nickel-iron double metal hydroxide electrocatalyst.
[0011] An electrochemical preparation method of a carbon-supported nickel-iron bimetallic hydroxide catalyst for electrocatalytic nitrate reduction to synthesize ammonia is as follows: the carbon-supported nickel-iron bimetallic hydroxide electrocatalyst is cut into 1cm×1cm thin sheets as cathode plates, 1cm×1cm commercial platinum sheet electrodes are used as anode plates, and the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), and assembled into a three-electrode system H-type electrolytic cell, the cathode is loaded with a mixed solution of 1-3009mM / L KNO3 and 0.1M / L KOH, wherein the concentration of KOH in the mixed solution is 0.1M / L, and the concentration of KNO3 does not exceed its saturation concentration (≤3009mM / L). The anode is loaded with an equal amount of 0.1M / L KOH solution, and assembled into a reaction cell. Turn on the gas switch and charge at 10-50mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on, and the voltage was set to -0.6V to -2.3V for 1-4 hours of electrolysis. After the reaction was completed, the cathode pool solution was used to detect the ammonia concentration of the electrolyte after the reaction using indophenol blue spectrophotometry and an ammonia sensitive electrode, and the Faraday efficiency and ammonia yield were calculated.
[0012] Beneficial effects of the present invention:
[0013] The carbon paper used in the present invention has abundant oxygen vacancies and defect sites, which is beneficial to NO3 - To NO2 -The conversion of , which is also the rate-determining step of NO3RR. The addition of auxiliary agents such as sodium fluoride, ammonium chloride, ammonium fluoride (ammonium bifluoride) in the electrodeposition solution plays a role in surface modification. The ions act as templates in the synthesis of double metal hydroxides, so that the synthesized Ni-Fe LDH forms a flaky corolla structure on the surface of carbon paper. Urea (sodium hydroxide) decomposes into ammonium and carbonate during the electrodeposition process, providing an alkaline environment for the synthesis of double metal hydroxides, and carbonate exists in the catalyst as an intercalated anion. This synthesized double metal hydroxide catalyst can effectively inhibit the occurrence of hydrogen evolution side reactions for the NO3RR reaction. At the same time, the combination of abundant oxygen vacancies on the surface of carbon fiber paper and the active sites of double metal hydroxides synergistically improves the Faraday efficiency. In addition, the excellent cycle stability of the supported double metal hydroxide prepared by the electrodeposition method can be used for long-term NO3RR processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The comparison chart of the synthetic ammonia yield and Faraday efficiency of materials synthesized by different ratios of nickel and iron in the electrodeposition solution of Examples 1, 2, 3 and Comparative Examples 1 and 2;
[0015] Figure 2 The effect of different catalyst loadings on the synthetic ammonia concentration and Faraday efficiency of Examples 4, 5 and 6;
[0016] Figure 3 The graphs are the effects of different applied voltages on the concentration of synthetic ammonia and the Faraday efficiency in Examples 7, 8 and 9;
[0017] Figure 4 This is a comparison chart of the synthetic ammonia yield and Faraday efficiency of different nitrate electrolyte concentrations in Examples 10, 11, and 12;
[0018] Figure 5 The performance of the catalyst formed by the electrodeposition operation in Example 13 was compared with that of a blank hydrophilic carbon paper catalyst. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0020] Comparative Example 1 (Iron Only)
[0021] Ferric nitrate nine hydrate, ammonium fluoride, and urea (concentrations are 0.1M, 1.6mM, and 4mM, respectively) are quickly stirred with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (voltage is set to -1V, temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of a 0.1M KOH solution. Turn on the gas switch at 10mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.3V for continuous reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, when the electrodeposition liquid is pure iron solution, the prepared Fe(OH)3 / CC can achieve a Faraday efficiency close to 100% and a high efficiency of 125 nmol s -1 cm -2 However, due to the Fe(OH)3 / CC 3+ Compared with NiFe LDH / CC, the cycle stability is poor. After 10 cycle tests, the catalyst performance dropped to 60% of the initial value, so it is not an ideal catalyst.
[0022] Comparative Example 2 (Nickel Only)
[0023] Nickel nitrate hexahydrate, ammonium bifluoride, and sodium hydroxide (concentrations are 0.1M, 1.6mM, and 4mM, respectively) are quickly stirred with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure method (the voltage is set to -1V, and the temperature is constant at 25°). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of a 0.1MKOH solution. Turn on the gas switch at 10mL min -1High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.3V for continuous reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, when the electrodeposition liquid is pure iron solution, the prepared Ni(OH)2 / CC can achieve a Faraday efficiency of 51% and a carbonization rate of 46 nmols / s. -1 cm -2 ammonia yield.
[0024] Example 1 (3:1)
[0025] The effects of different proportions of the carbon-supported nickel-iron bimetallic hydroxide catalyst shown in the present invention on the NO3RR performance were investigated. The specific operation is as follows: nickel nitrate hexahydrate, ferric nitrate nonahydrate, sodium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell mentioned above, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (voltage is set to -1V, temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of a 0.1M KOH solution. Turn on the gas switch at 10mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.1V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 1 As shown in the figure, the present invention prepares carbon-supported iron-based catalysts, carbon-supported nickel-based catalysts, and carbon-supported nickel-iron bimetallic hydroxide catalysts with ratios of 2:1, 3:1, and 4:1, respectively. When the nickel-iron ratio is 3:1, the catalytic performance is better, and the Faraday efficiency and ammonia yield are 96% and 90nmol s, respectively. -1 cm -2 The above results show that the ratio of nickel to iron in the catalyst is an important factor affecting the performance of carbon-supported nickel-iron double hydroxide catalyst for ammonia synthesis.
[0026] Example 2 (4:1)
[0027] Nickel nitrate hexahydrate, ferric nitrate nonahydrate, sodium chloride, and urea (concentrations are 0.8mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (voltage is set to -1V, temperature is constant at 25°). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven to dry for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of 0.1M KOH solution. Turn on the gas switch at 10mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.3V for continuous reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, when the nickel-iron ratio of the electrodeposition solution is 4:1, the prepared Ni4Fe1 LDH / CC can achieve a Faradaic efficiency of 83% and a carbonization rate of 69 nmol s -1 cm -2 ammonia yield.
[0028] Example 3 (2:1)
[0029] Nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium chloride, and urea (concentrations are 0.4mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (voltage is set to -1V, temperature is constant at 25°). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven to dry for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of 0.1M KOH solution. Turn on the gas switch at 10mL min -1High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.3V for continuous reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, when the nickel-iron ratio of the electrodeposition solution is 2:1, the prepared Ni2Fe1 LDH / CC can achieve a Faradaic efficiency of 80% and a carbonization rate of 81 nmol s -1 cm -2 ammonia yield.
[0030] Example 4 (deposition time is 0 min)
[0031] The effect of different loadings of the carbon-supported nickel-iron double metal hydroxide catalyst shown in the present invention on the performance of NO3RR is explored. The specific operation is as follows: nickel nitrate hexahydrate, iron nitrate nonahydrate, ammonium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the above-mentioned pre-assembled electrodeposition cell, and the electrodeposition is carried out for 0min by constant temperature and pressure (voltage is set to -1V, temperature is 25° constant temperature) mode. After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6h. The carbon-supported nickel-iron double metal hydroxide catalyst obtained above is used as the cathode plate, the anode plate adopts a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is loaded with 30mL of 0.1M KNO3 and 0.1M KOH mixed solution, and the anode is loaded with 30mL of 0.1M KOH solution. Turn on the gas switch and flow at 10 mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -0.6V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 2 When the deposition time is 0 min, the catalyst loading is 0 mg cm -2 After the reaction is completed, the ammonia concentration in the electrolyte is 5.4 mg / L and the Faraday efficiency is 10%.
[0032] Example 5 (deposition time is 5 min)
[0033] The effect of different loadings of the carbon-supported nickel-iron double metal hydroxide catalyst shown in the present invention on the performance of NO3RR is explored. The specific operation is as follows: nickel nitrate hexahydrate, iron nitrate nonahydrate, ammonium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the above-mentioned pre-assembled electrodeposition cell, and the electrodeposition is carried out for 5min by constant temperature and pressure (voltage is set to -1V, temperature is 25° constant temperature) mode. After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6h. The carbon-supported nickel-iron double metal hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is loaded with 30mL of 0.1M KNO3 and 0.1M KOH mixed solution, and the anode is loaded with 30mL of 0.1M KOH solution. Turn on the gas switch and flow at 10 mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -0.6V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 2 As time goes by, the amount of catalyst attached to the hydrophilic carbon paper increases from 0 mg cm -2 Up to 7 mg cm -2 , but its catalytic performance first increases and then decreases. -2 The optimal Faradaic efficiency and ammonia concentration reached 43% and 55 mg / L, respectively, and then decreased to 19% and 9.7 mg / L. Therefore, the optimal loading amount of carbon-supported nickel-iron double metal hydroxide electrocatalyst for synthesizing ammonia is 0.4 mg cm -2 .
[0034] Example 6 (deposition time is 60 min)
[0035] The effect of different loadings of the carbon-supported nickel-iron double metal hydroxide catalyst shown in the present invention on the performance of NO3RR is explored. The specific operation is as follows: nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the above-mentioned pre-assembled electrodeposition cell, and the electrodeposition is carried out for 60min by constant temperature and pressure (voltage is set to -1V, temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6h. The carbon-supported nickel-iron double metal hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is loaded with 30mL of 0.1M KNO3 and 0.1M KOH mixed solution, and the anode is loaded with 30mL of 0.1M KOH solution. Turn on the gas switch and flow at 10 mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -0.6V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 2 When the deposition time is 60 min, the catalyst loading is 7 mg cm -2 After the reaction is completed, the electrolyte ammonia concentration is 13.5 mg / L and the Faraday efficiency is 18%.
[0036] Example 7 (This example is the above voltage 0.6-2.3, the point value is -1.1V)
[0037] The effects of different loadings of the carbon-supported nickel-iron bimetallic hydroxide catalyst shown in the present invention on the NO3RR performance were investigated. The specific operation is as follows: nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 2mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell mentioned above, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (the voltage is set to -1V, and the temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of a 0.1M KOH solution. Turn on the gas switch at 10mL min -1High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.1V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, at -1.1 V, the Faradaic efficiency and ammonia yield are close to 100% and 150 nmol s -1 cm -2 As the electrolysis voltage increases, although the ammonia yield does not change much, the Faraday efficiency decreases slightly due to the intense competition for hydrogen evolution. The results show that a higher yield and the maximum Faraday efficiency can be achieved when the reaction is carried out at -1.1V.
[0038] Example 8 (This example is the above voltage -0.6--2.3, the point value is -0.6V)
[0039] The effects of different loadings of the carbon-supported nickel-iron bimetallic hydroxide catalyst shown in the present invention on the NO3RR performance were investigated. The specific operation is as follows: nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 1mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell mentioned above, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (the voltage is set to -1V, and the temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of a 0.1M KOH solution. Turn on the gas switch at 10mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -0.6V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, at -0.6 V, the Faradaic efficiency and ammonia yield are close to 100% and 47 nmol s -1 cm -2 .
[0040] Example 9 (This example is the above voltage 0.6-2.3, the point value is -2.3V)
[0041] The effects of different loadings of the carbon-supported nickel-iron bimetallic hydroxide catalyst shown in the present invention on the NO3RR performance were investigated. The specific operation is as follows: nickel sulfate, ferric sulfate, ammonium fluoride, and sodium hydroxide (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell mentioned above, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (voltage is set to -1V, temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of 0.1M KOH solution. Turn on the gas switch at 10mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -2.3V for continuous reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, at -2.3 V, the Faradaic efficiency and ammonia yield are close to 91% and 188 nmol s -1 cm -2 .
[0042] Example 10 (This example is the above 1-3009mM electrolyte concentration point value is 1mM)
[0043] The effect of the electrolyte concentration of the carbon-supported nickel-iron bimetallic hydroxide catalyst shown in the present invention on the NO3RR performance is explored. The specific operation is as follows: nickel acetate, ferric chloride, ammonium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the above-mentioned pre-assembled electrodeposition cell, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (the voltage is set to -1V, and the temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 1mM KNO3 and 0.1M KOH, and the anode is filled with 30mL of 0.1M KOH solution. Turn on the gas switch at 10mL min -1High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.1V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, when the KNO3 concentration is 1 mM, the Faraday efficiency reaches 7% and the ammonia yield reaches 38 nmol s -1 cm -2 .
[0044] Example 11 (This example is the above 1-3009mM electrolyte concentration point value is 1000mM)
[0045] The effect of the electrolyte concentration of the carbon-supported nickel-iron bimetallic hydroxide catalyst shown in the present invention on the NO3RR performance is explored. The specific operation is as follows: nickel acetate, ferric acetate, ammonium fluoride, and sodium hydroxide (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred evenly using a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the above-mentioned pre-assembled electrodeposition cell, and the electrodeposition is carried out for 5 minutes using a constant temperature and constant pressure (the voltage is set to -2V, and the temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 1000mM KNO3 and 0.1M KOH, and the anode is filled with 30mL of a 0.1M KOH solution. Turn on the gas switch at 10mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.1V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, as the electrolyte concentration continues to increase, the Faraday efficiency continues to rise, and the ammonia yield continues to increase from 1mM to 1000mM. When the KNO3 concentration is 1000mM, the Faraday efficiency reaches nearly 100%, and the ammonia yield reaches 142nmol s -1 cm -2 .
[0046] Example 12 (This example is the above 1-3009mM electrolyte concentration point value is a saturated potassium nitrate solution)
[0047] The effect of the electrolyte concentration of the carbon-supported nickel-iron bimetallic hydroxide catalyst shown in the present invention on the NO3RR performance is explored. The specific operation is as follows: nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride, and urea (concentrations are 0.6mM, 0.2mM, 1.6mM, and 4mM, respectively) are quickly stirred evenly with a magnetic stirrer to obtain a mixed solution, and the mixed solution is added to the pre-assembled electrodeposition cell mentioned above, and the electrodeposition is carried out for 5 minutes by constant temperature and pressure (voltage is set to -1V, temperature is 25° constant temperature). After the reaction is completed, the cathode plate is taken out, rinsed with deionized water, and placed in a 60° oven for drying for 6 hours. The carbon-supported nickel-iron bimetallic hydroxide catalyst obtained above is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a saturated KNO3 and 0.1M KOH mixed solution, and the anode is filled with 30mL of a 0.1M KOH solution. Turn on the gas switch at 10mL min -1 High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.1V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, as the electrolyte concentration continues to increase, the Faraday efficiency continues to rise, and the ammonia yield continues to increase from 1mM to 1000mM, but in saturated potassium nitrate solution, the ammonia yield drops to 101.69nmol s -1 cm -2 , the Faraday efficiency is close to 100%. Therefore, the optimal application concentration of the carbon-supported nickel-iron double metal hydroxide catalyst for synthesizing ammonia is 1000mM.
[0048] Example 13 (this example is a blank control)
[0049] The effect of the metal loading of the carbon-supported nickel-iron double hydroxide catalyst shown in the present invention on the NO3RR performance was investigated. The specific operation is as follows: the hydrophilic carbon paper that has not been subjected to the above-mentioned electrodeposition operation is used as the cathode plate, the anode plate uses a commercial Pt sheet electrode, the reference electrode is Ag / AgCl (the filling liquid is a saturated KCl solution), the cathode cell is filled with 30mL of a mixed solution of 0.1M KNO3 and 0.1M KOH, and the anode is filled with 30mL of a 0.1M KOH solution. Turn on the gas switch and charge at 10mL min -1High-purity argon was continuously introduced at a flow rate. After 30 minutes, the power switch of the electrochemical workstation was turned on and the electrolysis voltage was set to -1.1V to continue the reaction. After the reaction was completed, the cathode cell electrolyte was collected and the ammonia concentration of the electrolyte after the reaction was detected by indigo blue spectrophotometry and ammonia sensitive electrode. The Faraday efficiency and ammonia yield were calculated. The results are as follows: Figure 3 As shown in the figure, the hydrophilic carbon paper without the deposition of nickel-iron metal oxide has a Faraday efficiency of 53% and an ammonia yield of 42 nmol s -1 cm -2 The carbon-supported nickel-iron double hydroxide electrocatalyst with a nickel-iron ratio of 3:1 has a Faradaic efficiency of 90% and an ammonia yield of 78 nmol s -1 cm -2 It is significantly higher than that of hydrophilic carbon paper. Therefore, the doping of nickel-iron metal is beneficial to improve the catalytic activity of hydrophilic carbon paper.
[0050] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An electrochemical preparation method of a carbon-supported nickel-iron double metal hydroxide catalyst for electro-reduction of nitrate to synthesize ammonia, characterized in that: The following steps are involved: Step 1, dissolving nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride and urea in deionized water respectively, and quickly stirring with a magnetic stirrer to obtain a mixed solution; wherein the concentrations of nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride and urea in the mixed solution are 0.4-0.8mM, 0.2mM, 1-2mM and 4mM respectively; Step 2, using the electrode sandwiched with hydrophilic carbon paper as the cathode plate, using the commercial platinum sheet electrode as the anode plate, using the reference electrode as Ag / AgCl and assembling an electrochemical workstation into an electrodeposition cell; Step 3: Add the mixed solution into a pre-assembled electrodeposition cell, set the voltage in the range of -1V to -2V, keep the temperature at 25°C, and conduct the electrodeposition reaction in a constant voltage manner for no more than 60 minutes. After the reaction, take out the cathode plate, rinse it with deionized water, put it in an oven to dry, and then take it out to obtain a carbon-coupled nickel-iron-based electrocatalyst.
2. The method for preparing a carbon-coupled nickel-iron-based catalyst for electrocatalytic nitrate reduction ammonia synthesis according to claim 1, characterized in that: The nickel nitrate hexahydrate described in step 1 can be replaced by nickel sulfate or nickel acetate.
3. The method for preparing a carbon-coupled nickel-iron-based catalyst for electrocatalytic nitrate reduction ammonia synthesis according to claim 1, characterized in that: The ferric nitrate nonahydrate described in step 1 can be replaced by ferric sulfate, ferric acetate, or ferric chloride.
4. The method for preparing a carbon-coupled nickel-iron-based catalyst for electrocatalytic nitrate reduction ammonia synthesis according to claim 1, characterized in that: The ammonium fluoride described in step 1 can be replaced by ammonium bifluoride, sodium fluoride, sodium chloride, or ammonium chloride.
5. The method for preparing a carbon-coupled nickel-iron-based catalyst for electrocatalytic nitrate reduction ammonia synthesis according to claim 1, characterized in that: The urea described in step 1 can be replaced by sodium hydroxide.
6. Use of a carbon-coupled nickel-iron-based catalyst for electrocatalytic nitrate reduction ammonia synthesis obtained by the preparation method according to any one of claims 1 to 5, characterized in that: The carbon-coupled nickel-iron-based electrocatalyst was cut into thin sheets as the cathode plate, the commercial platinum sheet electrode was used as the anode plate, and the reference electrode was Ag / AgCl. They were assembled into an H-type electrolytic cell with a three-electrode system. The cathode was loaded with a mixed solution of KNO3 and KOH, and the anode was loaded with an equal amount of KOH solution to assemble into a reaction cell. Turn on the gas switch, continuously introduce high-purity argon gas, turn on the power switch of the electrochemical workstation, set the voltage to -0.6V to -2.3V and continue electrolysis for 1-4h.
